Alkylpyridinium Tetrahalidometallate Ionic Liquids and Ionic Liquid Crystals: Insights into the Origin of Their Phase Behavior. Issue 48 (5th December 2017) - Abouserie, Ahed; Zehbe, Kerstin; Metzner, Philipp; Kelling, Alexandra; Günter, Christina; Schilde, Uwe; Strauch, Peter; Körzdörfer, Thomas; Taubert, Andreas
Abstract : Six N ‐alkylpyridinium salts [C n Py]2 [MCl4 ] ( n = 4 or 12 and M = Co, Cu, Zn) were synthesized, and their structure and thermal properties were studied. The [C4 Py]2 [MCl4 ] compounds are monoclinic and crystallize in the space group P 21 / n . The crystals of the longer chain analogues [C12 Py]2 [MCl4 ] are triclinic and crystallize in the space group P 1 . Above the melting temperature, all compounds are ionic liquids (ILs). The derivatives with the longer C12 chain exhibit liquid crystallinity and the shorter chain compounds only show a melting transition. Consistent with single‐crystal analysis, electron paramagnetic resonance spectroscopy suggests that the [CuCl4 ] 2– ions in the Cu‐based ILs have a distorted tetrahedral geometry. Abstract : The study describes six alkylpyridinium tetrachloridometallate (M = Cu, Co, Zn) ionic liquids (ILs), their crystal structures, and thermotropic phase behavior. The work provides insight into the reasons for the different behavior of copper‐based ILs vs. their cobalt and zinc‐based counterparts.